On the Neotropical Brincadorus: redescription, new species, taxonomic key and description of a related new genus (Insecta: Hemiptera: Cicadellidae: Deltocephalinae) - Camisão, Beatriz M.; Zahniser, James N.; Takiya, Daniela M. (Zootaxa, 2024)
The Neotropical genus Brincadorus Oman, 1938 is redescribed, and five new species are described and illustrated. Brincadorus cruceno sp. nov., from Bolivia and Peru, can be differentiated by the long and slender aedeagus, with a pre-apical dorsal spine and apex curved downwards. Brincadorus gracilis sp. nov., from Ecuador and Peru, can be distinguished by the slender subgenital plates, aedeagus with slender shaft and basidorsal processes without a preapical tooth. Brincadorus limoncocha sp. nov. from Ecuador, can be differentiated by the robust aedeagus shaft, and bifurcate basidorsal processes. Brincadorus quincemil sp. nov., from Peru, can be distinguished by the bifurcate apex of the subgenital plates, and aedeagus basidorsal process with a preapical dorsal tooth. Brincadorus yanayacu sp. nov., from Ecuador, can be distinguished by the thorn-like apex of the subgenital plates, and short aedeagus, without processes. A key to species is provided, and a female is illustrated and described for the first time. New records for Ecuador and Peru are provided. A new genus that shares similarities with Brincadorus is described. Saltadorus gen. nov. can be distinguished by the smaller size, male pygofer with a pair of long inner lateral processes arising sub-basally on the dorsal region and extending beyond the pygofer apex, widely separated and elongated subgenital plates, and robust aedeagus with a conspicuous sclerotized gonoduct protruding from the atrium. Saltadorus blahniki sp. nov., from Peru, can be identified by the elongated male pygofer, and aedeagus without processes. Saltadorus dietrichi sp. nov., from Peru, can be distinguished by the shorter male pygofer, and aedeagus with a pair of subapical dorsal teeth. Based on the results of recent phylogenomic analyses, Brincadorus is removed from Bahitini and, along with Saltadorus, is considered unplaced to tribe in Deltocephalinae, pending further study.